First-time detection of Mycobacterium bovis in livestock tissues and milk in the West Bank, Palestinian Territories. - Suheir Ereqat; Abedelmajeed Nasereddin; Hagai Levine; Kifaya Azmi; Amer Al-Jawabreh; Charles L Greenblatt; Ziad Abdeen; Gila Kahila Bar-Gal (Public Library of Science (PLoS), 2013)
BACKGROUND: Bovine tuberculosis, bTB, is classified by the WHO as one of the seven neglected zoonontic diseases that cause animal health problems and has high potential to infect humans. In the West Bank, bTB was not studied among animals and the prevalence of human tuberculosis caused by M. bovis is unknown. Therefore, the aim of this study was to estimate the prevalence of bTB among cattle and goats and identify the molecular characteristics of bTB in our area. METHODOLOGY/PRINCIPAL FINDINGS: A total of 208 tissue samples, representing 104 animals, and 150 raw milk samples, obtained from cows and goats were examined for the presence of mycobacteria. The tissue samples were collected during routine meat inspection from the Jericho abattoir. DNA was extracted from all samples, milk and tissue biopsies (n = 358), and screened for presence of TB DNA by amplifying a 123-bp segment of the insertion sequence IS6110. Eight out of 254 animals (3.1%) were found to be TB positive based on the IS6110-PCR. Identification of M. bovis among the positive TB samples was carried out via real time PCR followed by high resolution melt curve analysis, targeting the A/G transition along the oxyR gene. Spoligotyping analysis revealed a new genotype of M. bovis that was revealed from one tissue sample. SIGNIFICANCE: Detection of M. bovis in tissue and milk of livestock suggests that apparently healthy cattle and goats are a potential source of infection of bTB and may pose a risk to public health. Hence, appropriate measures including meat inspection at abattoirs in the region are required together with promotion of a health campaign emphasizing the importance of drinking pasteurized milk. In addition, further studies are essential at the farm level to determine the exact prevalence of bTB in goats and cattle herds in the West Bank and Israel.